Formulation And Sensory Evaluation of Waterchestnut Flour Laddoo - Shalini; Raghav , Pramod K (Journal of Postharvest Technology, 2022)
After chestnut flour was used to prepare Ladoo by incorporating processed water chestnut through sun drying, water chestnut flour Ladoo was standardized with different percentages of water chestnut flour. The percentages used were 0% (T0 as control), 5% (SDT1), 10% (SDT2), 15% (SDT3), and 20% (SDT4), respectively. Water chestnut flour incorporated Ladoo with 0% water chestnut flour was treated as the control. The nutritional contents of the sun-dried water chestnut flour were evaluated using AOAC methods. The proximate composition of SDT (sun-dried water chestnut flour treatment) for moisture content, protein, fat, total ash, crude fiber, and carbohydrate were 11.02 g, 12.42 g, 3.44 g, 2.93 g, 0.54 g, and 70.19 g, respectively. Water chestnut flour is a potential source of potassium and calcium, with levels of 1298.64 mg/100g and 89.26 mg/100g, respectively. The water chestnut flour showed good antioxidant content. In the evaluation of sensory characteristics of water chestnut Ladoo, a significant difference (P<0.05) was found among all treatments (SDT1, SDT2, SDT3, and SDT4). The differences were observed in terms of appearance/color, texture, taste, flavor, and aftertaste. The various products were also found to be a good source of nutrients, particularly in terms of protein, carbohydrate, minerals, and antioxidants. The incorporation of sun dried water chestnut flour Ladoo with 10% was found to be effective in maintaining better health conditions for everyone.